Recommendations on management of the SARS-CoV-2 coronavirus pandemic (Covid-19) in kidney transplant patients() - López, Verónica (Nefrología (English Edition), 2020)
The SARS-CoV-2 (Covid-19) coronavirus pandemic is evolving very quickly and means a special risk for both immunosuppressed and comorbid patients. Knowledge about this growing infection is also increasing although many uncertainties remain, especially in the kidney transplant population. This manuscript presents a proposal for action with general and specific recommendations to protect and prevent infection in this vulnerable population such as kidney transplant recipients.